The population biology and transmission dynamics of Loa loa - Whittaker,C; Walker,M; Pion,SDS; Chesnais,CB; Boussinesq,M; Basanez,MG (Trends in Parasitology, 2018)
Endemic to Central Africa, loiasis – or African eye worm (caused by the filarial nematode Loa loa) – affects more than 10 million people. Despite causing ocular and systemic symptoms, it has typically been considered a benign condition, only of public health relevance because it impedes mass drug administration-based interventions against onchocerciasis and lymphatic filariasis in co-endemic areas. Recent research has challenged this conception, demonstrating excess mortality associated with high levels of infection, implying that loiasis warrants attention as an intrinsic public health problem. This review summarises available information on the key parasitological, entomological, and epidemiological characteristics of the infection and argues for the mobilisation of resources to control the disease, and the development of a mathematical transmission model to guide deployment of interventions.